Alginate in Wound Dressings - Blessing Atim Aderibigbe; Buhle Buyana (MDPI AG, 2018)
Alginate is a biopolymer used in a variety of biomedical applications due to its favourable properties, such as biocompatibility and non-toxicity. It has been particularly attractive in wound healing applications to date. It can be tailored to materials with properties suitable for wound healing. Alginate has been used to prepare different forms of materials for wound dressings, such as hydrogels, films, wafers, foams, nanofibres, and in topical formulations. The wound dressings prepared from alginate are able to absorb excess wound fluid, maintain a physiologically moist environment, and minimize bacterial infections at the wound site. The therapeutic efficacy of these wound dressings is influenced by the ratio of other polymers used in combination with alginate, the nature of cross linkers used, the time of crosslinking, nature of excipients used, the incorporation of nanoparticles, and antibacterial agents. This review provides a comprehensive overview of the different forms of wound dressings containing alginate, in vitro, and in vivo results.